2023
DOI: 10.1186/s13047-023-00656-6
|View full text |Cite
|
Sign up to set email alerts
|

Objectively assessed long‐term wearing patterns and predictors of wearing orthopaedic footwear in people with diabetes at moderate‐to‐high risk of foot ulceration: a 12 months observational study

Stein H. Exterkate,
Manon Jongebloed‐Westra,
Peter M. ten Klooster
et al.

Abstract: Background Orthopaedic footwear can only be effective in preventing diabetic foot ulcers if worn by the patient. Robust data on long-term wearing time of orthopaedic footwear are not available, and needed to gain more insights into wearing patterns and associated factors (i.e. participants’ demographic, disease-related characteristics, and footwear usability). We aimed to objectively assess long-term wearing patterns and identify factors associated with wearing orthopaedic footwear in people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Risk-factor studies have shown that factors like diabetes history, body mass index, footwear appearance, being indoors, patient expectations towards efficacy, and postural issues influence adherence rates, although the explained variance is still not very high and 25% at maximum. 11,[15][16][17][18][19][20][21][22] Nevertheless, these factors should be considered and where modifiable targeted in assessing treatment adherence and determining the treatment plan to improve adherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk-factor studies have shown that factors like diabetes history, body mass index, footwear appearance, being indoors, patient expectations towards efficacy, and postural issues influence adherence rates, although the explained variance is still not very high and 25% at maximum. 11,[15][16][17][18][19][20][21][22] Nevertheless, these factors should be considered and where modifiable targeted in assessing treatment adherence and determining the treatment plan to improve adherence.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that many patients do not wear their offloading device or prescribed footwear as recommended may be related to demographic, psycho‐social, environmental, contextual and device or shoe‐related factors. Risk‐factor studies have shown that factors like diabetes history, body mass index, footwear appearance, being indoors, patient expectations towards efficacy, and postural issues influence adherence rates, although the explained variance is still not very high and 25% at maximum 11,15–22 . Nevertheless, these factors should be considered and where modifiable targeted in assessing treatment adherence and determining the treatment plan to improve adherence.…”
Section: Introductionmentioning
confidence: 99%